The Influence of English Teacher Competence on Learning Achievement of High School Students in Purwokerto - Prayogo Hadi Sulistio; Tuti Purwati; Usep Muttaqin (English Language in Focus (ELIF), 2021)
This study aims to examine the relationship between the competence of English teachers and the learning achievement of high school students in Purwokerto. Teacher competence is one of the main supporting things in achieving educational goals. Furthermore, student achievement becomes a barometer of achievement of educational goals as seen from the scores of the National English Test. Seeing these facts, this study tries to find a relationship between teacher competence and student achievement. Researchers used descriptive analysis techniques and simple regression techniques. Descriptive analysis is used to explain teacher competence through answers to the questionnaire was given and simple regression analysis is used to examine the relationship between the competence of English teachers and student achievement. In addition, the items in the questionnaire were also tested for their validity and reliability. Based on the findings, H1 is rejected, so it can be concluded that teacher competence does not have a significant positive influence on student achievement.